(untitled) (Journal of National Institute of Ophthalmology, 2026)
Background: World Health Organization defines low vision patients as a person who has impairment of visual functioning even after treatment and/or standard refractive correction, and visual acuity of the better eye less than 6/18 to light perception, or a visual field less than 10 degrees from the point of fixation, but who uses, or is potentially able to use, vision for the planning and/or execution of a task for which vision is essential. The National Blindness and Low Vision Prevalence Survey of Bangladesh, 2000 revealed that the prevalence percentage of low vision was 3.2 % and blindness 1.0%. Population growth and ageing will increase the risk that more people acquire vision impairment. Objective: To assess visual outcome of low vision patients with optical low vision devices attending low vision clinic of National Institute of Ophthalmology and Hospital, Dhaka, Bangladesh. Methodology: This prospective observational study was conducted in low vision clinic of National Institute of Ophthalmology and hospital from April, 2018 to September, 2020. The study included 48 low vision patients aged 10-56 years who had best corrected visual acuity (BCVA) 6/60 or more in the better eye. Selected patients underwent detailed history taking and thorough ocular as well as systemic examination. Optical low vision devices (monocular or bioptic telescopes, handheld or bar magnifier and prism spectacles) were prescribed in all patients. They were evaluated without low vision aids then immediately and 3 months after prescription of optical low vision devices. Best corrected distance and near visual acuity and contrast sensitivity were assessed in each follow-up. Data were recorded in a pre-designed data collection sheet and analyzed by using IBM SPSS Statistics version 26, paired ‘t’ tests were done to assess the level of significance. Results: The mean age of the study group was 25.79±12.14 years with the age range of 10-56 years. Out of 48 patients 32 (66.67%) were male. Mean value of best corrected visual acuity was for distance Log MAR unit 0.76±0.16 (about 6/36) for near Log MAR unit 0.65±0.22 (about N10/1.25M) and for contrast sensitivity Log CS unit 1.15±0.56. With optical low vision devices, mean value of visual acuity for distance immediately after prescription was Log MAR unit 0.41±0.19 and after 3 months 0.41±0.20, for near immediately after Log MAR unit 0.39±0.12 and after 3 months Log MAR unit 0.39±0.12, for contrast sensitivity immediately after Log CS unit 1.40±0.63 and after 3 months Log CS unit 1.40±0.63. Changes in distant and near visual acuity as well as contrast sensitivity in each follow-up was statistically significant (p<0.001). Optical low vision devices used for distant vision were 3X binocular telescopes (56.25% study subjects), 4X monocular telescope (27.08%), and 2.1X See TV binocular telescopes (16.67%). Optical low vision devices used for near vision were 3X handheld magnifier (89.58%), 1.5X bar magnifier (2.08%), base in prism spectacles (6.25%). Main causes of low vision were found to be macular dystrophy (27.1%), retinitis pigmentosa (20.8%), and myopic degeneration (14.6%). Conclusion: Visual acuity for distance and near as well as contrast sensitivity improves significantly with optical low vision devices in low vision patients. J.Natl.Inst.Ophthalmol.2024;7(2): 28-38